SCIENTIFIC IDEAS OF V.I. VERNADSKY ON GROUNDWATER GEOCHEMISTRY - Kuhar, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is dedicated to the activities of the V.I. Vernadsky in the field of studying of natural waters.